KEWENANGAN PEMERINTAH DALAM MELAKUKAN PENGAWASAN TERHADAP PENERBITAN IZIN NPPBKC BAGI PENGUSAHA MMEA DAN AKIBAT HUKUMNYA - Dharma Satya Varuni, Made; Arya Sumertayasa, Putu Gede (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014)
Government oversight of sales without having permission NPPBKC MMEA, the Directorate General of Customs and Excise with through the Office of Surveillance and Customs and Excise are there in these areas often go directly into the field to conduct licensing examinations for entrepreneurs who sell MMEA. This research using the emperis judicial conduct field research on the issues. The conclusions that can be drawn is that the government has the authority to supervise the entrepreneurs in conducting sales MMEA.
Keywords: Authority, Supervision, legal consequences